Can reforming the pre-university public educational sector in Egypt through privatization influence its quality? - Elzoughbi, Khaled (AUC Knowledge Fountain, 2018)
This research investigated the possibility of privatizing pre-university or basic education in Egypt. The pre-university education consists of three levels: primary education (six years), preparatory education (three years) and high school education (three years). The researcher employed the qualitative approach using semi-structured face-to-face interviews to collect answers to the research questions. The main findings of the research suggest that there are a huge demand on private schools in Egypt specially schools that teach English-based curriculum. Privatization in education could be one of the effective solutions to raise the quality of education, expand educational services and reduce the financial burden on the government. Recommendation suggests a gradual implementation to privatization of pre-university education in Egypt using the school vouchers system with taking in consideration concerns of teachers, schools managements, parents, students, and private sector.